An advanced approach to the system safety in sociotechnical systems - Zarei, Esmaeil; Khan, Faisal; Abbassi, Rouzbeh (Safety science, 2023)
•A systematic approach to identify and quantify PSFs importance on the performance of complex sociotechnical systems is proposed.•A holistic PSFs Taxonomy based on sociotechnical systems design is proposed.•The proposed model’s capability is tested on maintenance operations in the chemical process plants.•This study helps to allocate safety measures to improve resilience and safety performance. The safety performance of sociotechnical systems (STSs) and their main components (e.g., human, organization, and technology) vary due to numerous performance shaping factors (PSFs). However, previous research mainly focused on studying limited PSFs related to human functions, while organization and technology functions have often been ignored. This paper aims to propose a systematic approach to identify PSFs, quantify their importance level and influence on the performance of complex sociotechnical systems’ functions. To this end, we first developed a holistic PSFs Taxonomy based on sociotechnical systems design and then employed novel Interval-Valued Spherical Fuzzy Sets (IVSFS) and Best Worst Method to quantify the importance of performance. We tested the proposed model’s capability on maintenance operations in the chemical process plants and compared the model with the previous research considering fourteen criteria. The findings revealed the approach's effectiveness in dealing with epistemic uncertainty, vagueness, and fuzziness in the knowledge acquisition process. It revealed the critical safety investment factors among different sociotechnical elements and contributing factors to maintenance operations. This helps to effectively allocate safety countermeasures to improve resilience and system safety performance.